The innovations of new French contract law and it's comparing with Iranian law system - Jafar Nouri Youshanlooi; Abolfazl Shahin (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2018)
The reform of the French contract law occurred pursuant to the Ordinance No. 2016-131 of February 10, 2016 implements the reform of legal regime governing contractual obligations and evidence. For the purpose of simplification of French contract law and in the light of its compatibility with laws on international contracts, this Ordinance makes major changes to French contract law such as reinforcing the role of judges for securing contractual justice and increasing the power of unilateral consent for the purpose of economic efficiency of contract. French contract law has a great influence on Iranian contract law and Iranian jurists in the context of the contracts. Commentaries on Iranian Civil Code have paid a great attention to French law, which led to a close relationship between French contract law and its Iranian counterpart.  Therefore, this article aims to explore the effects of new French contract law on Iranian law